A comparison of para, meta, and ortho-carborane centred non-fullerene acceptors for organic solar cells. Issue 12 (1st March 2023) - Aniés, Filip; Furlan, Francesco; Qiao, Zhuoran; Pirela, Valentina; Bidwell, Matthew; Rimmele, Martina; Martín, Jaime; Gasparini, Nicola; Heeney, Martin
Abstract : Unveiling the impact of different structural isomers of carborane-containing non-fullerene acceptors on optoelectronic properties and organic photovoltaic performance. Abstract : We report the first examples of carborane-containing non-fullerene acceptors (NFAs), and their use in organic photovoltaic (OPV) devices. NFAs employing an A–D–A′–D–A type design centred around a central electron withdrawing carborane unit (A′), using either para, meta, or ortho -carborane isomers are reported. We demonstrate that the nature of the isomer has a major impact on device performance, despite minor differences in optoelectronic and morphological properties, with the use of ortho -carborane resulting in the highest device efficiencies. We further show that end-group fluorination is an efficient strategy to modulate energy levels and improve device performance of such NFAs.